The Role of Receivables Cash and Dividends in Stock Investment on the Indonesia Stock Exchange - Yulian Ade Chandra; Kartika Ayu Kinanti; Moh. Hudi Setyobakti (International Journal of Accounting and Management Research, 2023)
Investment plays an important role in a country's economy. How companies controlled by majority shareholders can establish a relationship of mutual need and mutual benefit with retail investors. Dividends can be a bridge for fair and proportional profit sharing. The ratio of receivables to cash and Dividend Per Share is important to be further investigated using statistical tests. The ratio of receivables to cash is a novelty in financial management research. If the ratio of receivables to cash is too high, it will create the potential for high dependence of the company on the collective receivables in the future to finance its operations. This article was created with the aim of gaining a strong understanding of the ratio of accounts receivable to cash and Dividend Per Share (DPS) and its relation to sharia-indexed stock prices. The method used in writing this article is descriptive qualitative method. Based on empirical studies and also analysis in the discussion, it shows that Dividend Per Share (DPS) has a large and crucial role in making decisions on stock buying and selling transactions made by investors. This can be interpreted that theoretically, Dividend Per Share (DPS) affects stock prices.